Impact of marketing strategy and tam on buyer attitudes on online platforms: A study on gen z marketplace users - Bagus Hari Sugiharto; Nafi’ah Nafi’ah; Ayniyatin Nadiyah; Fairuz Rania (Indonesia Accounting Research Journal, 2025)
This paper looks at how simplicity, confidence, discounts, free shipping coupons, and endorsements affect Gen Z's buying choices and consumer behavior in marketplaces. The findings reveal that while free shipping vouchers are detrimental, trust is the most powerful influence. These results enable companies to create successful marketing plans. The study results show that the main influence on buying choices and consumptive behavior is consumer confidence in market platforms. Though to a lesser degree, shopping choices are also influenced by perceived simplicity of use, marketing tactics, and endorser support. Interestingly, shopping interest was negatively affected by free shipping coupons. On the other hand, for consumptive behaviour, only trust and promotions showed a major impact. These results imply that digital marketing plans should give consumer trust first priority. By investigating the particular effects of perceived simplicity, confidence, incentives, free shipping coupons, and endorsements on Generation Z's behavior in marketplaces, this paper makes a special contribution. Unexpectedly, the results show that while endorsements only influence buying choices—not consumptive behavior—two seldom recorded events in prior studies, free shipping vouchers really harm consumers. By revealing the unique dynamics of Gen Z—who are impulsive yet critical—this study closes a gap in the literature and offers insightful analysis for digital marketing plans.